Considerations on the cross-cultural adaptation process and validation of measurement questionnaire - Rucco Penteado Detregiachi, Cláudia; Rezek Andery Altran , Bruna (Seven Editora, 2023)
Translating an existing instrument demands a shorter period than developing a new one (HUNT et al., 1991). The intention when translating a questionnaire is to develop another version of the instrument with equivalence to the original (HILTON; SKRUTOWSKI, 2002). Cross-cultural adaptation is defined as the adjustment of a questionnaire to another specific language/dialect of a country or region (AARONSON et al., 2002) and to its respective cultural context and lifestyle (GUILLEMIN; BOMBARDIER; BEATON, 1993). The translation of instruments from one language to another should not be done in a linear process, since there are several options for translating a word or phrase and there may not be an exactly equivalent translation for a given term (COSTER; MANCINI, 2015). Thus, in this translation process, the instruments should not be literally translated, but culturally adapted to the target population, in order to maintain the validity of their content at a conceptual level even in different cultures (BEATON et al., 2000 ; REICHENHEIM; MORAES, 2007). DOI: https://doi.org/10.56238/devopinterscie-106